(untitled) (International Journal of Engineering and Computer Science, 2018)
A wireless sensor network (WSN) is collection of sensor nodes located at unattended areas. To fetch the data from sensor nodes, static or dynamic agents can be used. The dynamic agent is used instead of a static agent by implementing the Genetic Algorithm. In this algorithm, a network is subdivided in N number of clusters and cluster head is elected for each cluster which directly communicates the information to sink. Mobile agent (i.e. dynamic agent) moves in random fashion and fetch data from cluster heads. By this algorithm, network can remain alive for longer period of time as power consumption and packet loss rate will decrease. In this paper, dynamic sink along with usage of Genetic algorithm is being proposed